Lamivudine/dolutegravir dual therapy in HIV-infected, virologically suppressed patients - Maggiolo, Franco; Gulminetti, Roberto; Pagnucco, Layla; Digaetano, Margherita; Benatti, Simone; Valenti, Daniela; Callegaro, Annapaola; Ripamonti, Diego; Mussini, Cristina (BMC infectious diseases, 2017)
Background Little is known about the applicability of dual treatments based on integrase inhibitors. We explored the combination of lamivudine + dolutegravir as an option when switching from standard cART in virologically suppressed patients. Methods In this prospective cohort we enrolled patients previously switched to 3TC + DTG who were 18 years or older, with no previous resistance mutations to the used drugs, having a HIV-RNA <50 copies/ml for 6 months or longer, negative for HBsAg and on a stable (>6 months) cART. Results Ninety-four individuals were included. They were mostly men (77.7%) with a mean age of 53 years. They presented 159 co-morbidities including cardiovascular, bone, hepatic, kidney, and CNS diseases. Because of these pathologies, they took 207 non-ARV drugs (mean 2.2 per patient). Median duration of viral suppression was 77.5 months (IQR 61). All subjects were prospectively followed up to week 24 and all remained on dual therapy during the whole period. Neither virological failure, nor viral blip was detected. The median CD4 count rose from 658 cells/mcl (IQR 403) to 724 cells/mcl (IQR 401) ( P = 0.006) without a significant ( P = 0.44) change in the CD4/CD8 ratio. A significant ( P < 0.0001) increment of median creatinine from 0.87 mg/dl (IQR 0.34) to 0.95 mg/dl (IQR 0.29) was observed in the first 2 months but thereafter leveled on these values (1.00 mg/dl; IQR 0.35) ( P = 0.111 compared to 2 months). The lipid profile slightly improved. The daily cost of cART was significantly ( P < 0.0001) reduced of 6.89 euros (SD 6.10). Discussion Switching to a dual cART regimen based on lamivudine + dolutegravir maintains virological efficacy up to week 24, and is associated to slight improvements of the immunologic and metabolic status. The strategy allows to freely using concomitant medications for associated pathologies. The dual therapy is less expensive in economic terms. Conclusion Although still limited evidence exists, a dolutegravir-based dual therapy in combination with lamivudine shows promising results to be confirmed in larger controlled trials.